Multidimensional assessment and validation of digital competencies in university teacher education: a confirmatory factor analysis - Mario Rubén Chifla-Villón; Mayra Paola Chifla-Villón; Ericka Mailyn Suárez-Guartamber; Fabricio Guevara-Viejó (Frontiers in Education, 2025)
IntroductionThe digital era requires teaching competencies that transcend simple technological competence, promoting innovative and sustainable pedagogical approaches. This research evaluates and models the digital competencies of higher education teachers, highlighting their impact on student learning and the adoption of sustainable pedagogical strategies.MethodsData were collected from 166 Ecuadorian teachers using an adapted “DigCompEdu Check-In” questionnaire, which examined six competency domains: Professional Engagement, Digital Resources, Digital Pedagogy, Assessment and Feedback, Student Empowerment, and Facilitating Student Digital Competence. The reliability of the scales was confirmed with internal consistency indicators (Cronbach’s α from 0.77 to 0.91). In addition, a Confirmatory Factor Analysis (CFA) was performed to validate the dimensional structure of the competencies.ResultsDescriptive results showed that 29.09% of the participants identified themselves as “Leader” and 56.36% as “Pioneer” in digital competencies. The AFC presented excellent fit indices (CFI = 1.00, TLI = 1.00, RMSEA = 0.00), evidencing a solid structure. The relationship between “Facilitating students’ digital competence” and “Empowering students” was high (factor loading of 0.93), highlighting the multidimensional and interdependent nature of digital competencies. Significant covariances were observed, such as between “Professional engagement” and “Facilitating digital competence” (0.76), reflecting the interaction between pedagogy, technology and professional engagement.DiscussionThe findings revealed a strong synergy between advanced digital competencies and sustainable pedagogical practices, reinforcing the importance of frameworks such as DigCompEdu and TPACK for professional development. It is concluded that strengthening these competencies is key to preparing teachers for the challenges of the transforming higher education context.